Linking Toluene Degradation with Specific Microbial Populations in Soil - Hanson, Jessica R. (American Society for Microbiology, 1999)
Phospholipid fatty acid (PLFA) analysis of a soil microbial community was coupled with (13)C isotope tracer analysis to measure the community’s response to addition of 35 μg of [(13)C]toluene ml of soil solution(−1). After 119 h of incubation with toluene, 96% of the incorporated (13)C was detected in only 16 of the total 59 PLFAs (27%) extracted from the soil. Of the total (13)C-enriched PLFAs, 85% were identical to the PLFAs contained in a toluene-metabolizing bacterium isolated from the same soil. In contrast, the majority of the soil PLFAs (91%) became labeled when the same soil was incubated with [(13)C]glucose. Our study showed that coupling (13)C tracer analysis with PLFA analysis is an effective technique for distinguishing a specific microbial population involved in metabolism of a labeled substrate in complex environments such as soil.